DESIGNING TECHNICAL AND PROFESSIONAL COMMUNICATION strategies for the global community. - Andrews, Deborah C.; Tham, Jason C. K., 1990- ([S.l.] : ROUTLEDGE, 2021)
This concise and flexible core textbook integrates a design thinking approach, rhetorical strategies, and a global perspective to help students succeed as technical and professional communicators in today's multimodal, mobile, and global community. Design thinking and good communication practices are rooted in empathy and human values. The integrated approach fosters students' ability to address the complex problems they will face in their careers, where they will collaborate with people who present diverse expertise, cultures, languages, and values. This book introduces the knowledge and skills as well as agile activities that help students communicate on projects within local and global communities. Parts 1and 2introduce the strategies for design thinking, audience analysis, communicating ethically, collaborating professionally, and managing projects to define problems and implement solutions. In Parts3 and 4, students learn to compose content in text and visuals. They learn to structure and deliver content by choosing the right genre and selecting effectively from the communication options available in today's multimodal environment. Designing Technical and Professional Communication serves as a flexible core textbook for technical and professional communication courses. An instructor's manual containing exercises, sample syllabus, and guidance for teaching in a variety of settings is available online at www.routledge.com/9780367549602.
OCLC-licensed vendor bibliographic record.
Keywords: Communication of technical information -- Study and teaching (Higher); Communication -- Study and teaching (Higher); TECHNOLOGY / Technical Writing